Clinical microbiology laboratory isolates: prevalence and gender variation - Haddadin, Randa; Aladwan, Hala; Alkhawaldeh, Batool; Alsous, Mervat; Collier, Phillip (Jordan Journal of Pharmaceutical Sciences, 2021)
Data archives of clinical microbiology laboratory (CML) are a rich source of valuable information. In this study, CML data from two tertiary care hospitals in Jordan were reviewed, in order to identify the source prevalence of microorganisms and the dissemination of Extended Spectrum Beta-Lactamase (ESBL) bacteria. The association between gender and the microorganism or specimen source was investigated. Data collected from each hospital was screened and filtered according to predetermined exclusion criteria. Of 20726 records screened, 5547 valid specimens with positive growth were considered. From these specimens 7143 isolates were identified to genus or species level. The most common specimens were identified and their association with gender was statistically determined and discussed. The prevalence of microorganisms in different specimens was compared with the literature, and variation from the expected results was explained. In addition, some associations were observed between gender and the predominating microorganisms. High dissemination rate of ESBL-producing bacteria was observed among Gram-negative bacteria (57%), indicating serious challenges facing clinicians in finding suitable treatments. Reviewing CML data can aid in the study of trends in the dissemination of microorganisms in specific population groups and can aid clinicians in amending their treatment protocols.